Occurrence of Visceral Gout in a Peafowl (Pavocristatus) – A Case Report - Sushma H R; N. Pazhanivel; Ganne Venkata Sudhakar Rao (The Indian Veterinary Journal, 2024)
An adult peafowl was bought for post-mortem examination to Department of Veterinary Pathology, Madras Veterinary College, Chennai. Postmortem examination revealed white chalk material on the surface of the liver,pericardium and epicardium with thickened pericardium . Kidneys were enlarged, grey in color and slightly congested. Microscopic examination of the heart revealed multifocal tophi formation in the pericardium surrounded by inflammatory cells and pericardial hemorrhages and congestion. Kidneys revealed tubular epithelial cell degeneration, necrosis and dilatation of tubules. Tophi formation was noticed in proximal convoluted and distal convoluted tubules and mineralization was noticed in tubules. Liver had multifocal micro to macro-vesicular fatty degeneration and tophi formation in the hepatic capsule. Lung revealed congestion and tophi formation. Based on the gross and histopathological examination the condition was diagnosed as visceral gout.